2018
DOI: 10.1016/j.celrep.2017.12.022
|View full text |Cite|
|
Sign up to set email alerts
|

Interrogating the Spatiotemporal Landscape of Neuromodulatory GPCR Signaling by Real-Time Imaging of cAMP in Intact Neurons and Circuits

Abstract: Modulation of neuronal circuits is key to information processing in the brain. The majority of neuromodulators exert their effects by activating G protein coupled receptors (GPCR) that control the production of second messengers directly impacting cellular physiology. How numerous GPCRs integrate neuromodulatory inputs while accommodating diversity of incoming signals is poorly understood. In this study we develop an in vivo tool and analytical suite for analyzing GPCR responses by monitoring the dynamics of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 45 publications
1
46
1
Order By: Relevance
“…Finally, we investigated two representative mutants, V354A and S239N, in the endogenous setting of D1R-expressing striatal medium spiny neurons (D1R-MSNs) using CAMPER reporter mice specifically expressing cAMP sensor in D1R-MSNs ( Muntean et al., 2018 ). We observed that the V354A mutant exhibited increased basal cAMP levels compared with the wild-type; however, cAMP concentration in these neurons did not change in response to dopamine stimulation ( Figures 5 E–5H).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, we investigated two representative mutants, V354A and S239N, in the endogenous setting of D1R-expressing striatal medium spiny neurons (D1R-MSNs) using CAMPER reporter mice specifically expressing cAMP sensor in D1R-MSNs ( Muntean et al., 2018 ). We observed that the V354A mutant exhibited increased basal cAMP levels compared with the wild-type; however, cAMP concentration in these neurons did not change in response to dopamine stimulation ( Figures 5 E–5H).…”
Section: Resultsmentioning
confidence: 99%
“…Mice (C57BL/6) were housed under standard conditions on a 12-hour light/dark cycle with continuous access to food and water in a pathogen-free facility. The CAMPER mouse was generated previously ( Muntean et al., 2018 ). Mice were appropriately genotyped and not subject to any prior procedures.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We set out to develop a platform for expressing and recording FRET-based biosensors that was both simple to use and readily generalizable to other biosensors and animal models. While transgenic mice have been generated that express a number of FRET biosensors 3,14,29 , we opted to use adeno-associated viral vectors (AAVs) to drive biosensor expression, since this would allow our tools to be exploited in both rats and mice without the need to maintain colonies of transgenic animals. In this work, we used previously published FRET-based reporters for PKA and ERK1/2 referred to as AKAR and EKAR respectively 13 .…”
Section: Resultsmentioning
confidence: 99%